Resource use efficiency in commercial poultry production in Oyo State, Nigeria (2015)
Poultry is a major livestock subsector which offers the least expensive way of filling the protein gap in human nutrition. However, low productivity in poultry subsector of livestock industry and inadequate knowledge on efficiency of resource allocation have scared many interested farmers from investing fully in the enterprise. The study ascertained the determinants of poultry productivity and allocative efficiency of each of the major resource inputs in commercial poultry production in Oyo State. Primary data were collected using well structured questionnaires. A multistage sampling technique was used to sample 90 poultry farmers to represent the commercial poultry farmers in the study area. Data collected were analyzed by using descriptive statistics and production function model. The result showed 'that the poultry farmers in the study area were educated and quite experienced in poultry farming with an average of 8years. The number of birds raised, labour, feed and drugs/vaccines were found to be the most significant inputs in poultry production and thus, require special attention. Poultry production in the study area was found in stage two of production surface as indicated by Returns to Scale (RTS) of 0.798. The result further showed that flock size, labour, feed and drugs/vaccines had efficiency indices of 0.046, 0.960, 0.00095 and 0.587 respectively implying that these inputs were inefficiently allocated and utilized except labour that was close to the economic optimum. It is therefore recommended that there should be policies aimed at educating poultry farmers in the study area on efficient resource management techniques most importantly efficient administration of feeds and drugs/vaccines, adequate stocking density of flock and efficient management practices.